Patients with uHCC and Child-Pugh B8/9 also benefit from a combination of antiangiogenic agents and PD-1 inhibitors: a multicenter real-world study - Xiaoyan Ding; Xue Yin; Linlin Zheng; Lin Zhou; Junke Hu; Wei Sun; Lei Sun; Yanjun Shen; Ying Teng; Yawen Xu; Wendong Li; Mei Liu; et al. (Acta Oncologica)
Background and purpose: Patients with unresectable hepatocellular carcinoma (uHCC) and Child-Pugh grade B face limited treatment options and poor outcomes. This study aims to evaluate whether the effect and safety of combining tyrosine kinase inhibitors (TKIs) with progressive disease (PD)-1 inhibitors in uHCC patients with Child-Pugh B7 (CP7) and B8/9 (CP8/9) differ.